2016
DOI: 10.1111/pcmr.12537
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of long non‐coding RNAs in cutaneous melanoma

Abstract: Summary Malignant melanoma is a highly aggressive form of skin cancer, the incidence of which is rising rapidly. Although MAPK‐targeting therapies and immune checkpoint blockade are emerging as attractive therapeutic approaches, their utility is limited to only a subset of patients who often acquire resistance. A better understanding of the aetiologies and genetic underpinnings of melanoma is therefore critical for the development of adjuvant or alternative therapeutic strategies aimed at increasing the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 65 publications
0
43
0
Order By: Relevance
“…The incidence of MM is rising more rapidly than any other prevalent cancers [2]. MM accounts for the vast majority of skin cancer patient deaths [3]. MM has proclivity to metastasize, and patients with metastatic MM has a poor prognosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of MM is rising more rapidly than any other prevalent cancers [2]. MM accounts for the vast majority of skin cancer patient deaths [3]. MM has proclivity to metastasize, and patients with metastatic MM has a poor prognosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…BRAF-activated non-coding RNA (BANCR), a 693-bp lncRNA on chromosome 9, has been reported to exert oncogenic acvities in many cancers under some specific conditions, such as non-small cell lung cancer, papillary thyroid carcinoma and colorectal cancer (14)(15)(16). Recent studies reported that BANCR is abnormally overexpressed in human malignant melanoma cell lines and tissues, and promotes proliferation and migration in malignant melanoma (17,18). These results suggest the oncogenic role and potential of BANCR as a therapeutic target for melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Genomewide association studies have recently mapped a large proportion of disease‐ or trait‐associated single nucleotide polymorphisms outside the protein coding regions of the genome, often in or near genes transcribed into lncRNAs (Bartonicek et al, ; Gong, Liu, Zhang, Miao, & Guo, ). There are bona fide examples of lncRNA linked to one or multiple hallmarks of cancer in a variety of cancers, including melanoma, in which many emerge as regulators of the MAPK and PI3K pathways (for review, Huang et al, ; Leucci, Coe, Marine, & Vance, ; Schmitt & Chang, ; Tasharrofi & Ghafouri‐Fard, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are bona fide examples of lncRNA linked to one or multiple hallmarks of cancer in a variety of cancers, including melanoma, in which many emerge as regulators of the MAPK and PI3K pathways (for review, Huang et al, 2018;Leucci, Coe, Marine, & Vance, 2016;Schmitt & Chang, 2016;Tasharrofi & Ghafouri-Fard, 2018).…”
Section: Introductionmentioning
confidence: 99%